Effect of drying temperature on the functional properties of biodegradable CMC-based film for potential food packaging - Suderman, N.; Isa, M.I.N.; Sarbon, N.M. (Universiti Putra Malaysia, 2024)
The purpose of this study was to investigate the functional properties (thickness; water vapor permeability (WVP); film microstructure, tensile strength (TS) and biodegradability) of carboxymethyl cellulose (CMC)/gelatin (gel)/chitosan (chi) biocomposite film as influenced by different drying temperature (25 and 60 °C). Seven formulations (CMC/gel/chi) prepared were control (100/0/0), formulations A (80/20/0), B (80/0/20), C (80/10/10), D (60/20/20), E (60/30/10), and F (60/10/30). Different drying temperature resulted in different time taken for the film to dry. Results revealed that formulation F was optimal due to its high tensile strength and low WVP rate which support its biodegradability for both drying conditions. FTIR assay revealed a strong carboxyl group for CMC, which contributed to high biodegradability results (85.3 vs. 85.50%) for room vs. oven dried specimens, respectively. Such desirable characteristics demonstrated that film F holds remarkable potential as edible films material with enhanced positive impacts on the environment and community